2020
DOI: 10.1002/ijc.33150
|View full text |Cite
|
Sign up to set email alerts
|

Height, body mass index and prostate cancer risk and mortality by way of detection and cancer risk category

Abstract: Obesity is a risk factor for advanced, but not localised, prostate cancer (PCa), and for poor prognosis. However, the detection of localised PCa through asymptomatic screening might influence these associations. We investigated height and body mass index (BMI) among 431 902 men in five Swedish cohorts in relation to PCa risk, according to cancer risk category and detection mode, and PCa-specific mortality using Cox regression. Statistical tests were two-sided. Height was positively associated with localised in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
3
25
2
Order By: Relevance
“…Despite the lack of an association between BMI and more advanced PCa in our previous study, 5 we, and a large number of other studies, found a positive association between BMI and the risk of PCa‐specific mortality 6,18‐22 . Only a few studies reported findings for WC and PCa‐specific mortality, which varied from no association 23,24 to a positive association 3,6 .…”
Section: Introductioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Despite the lack of an association between BMI and more advanced PCa in our previous study, 5 we, and a large number of other studies, found a positive association between BMI and the risk of PCa‐specific mortality 6,18‐22 . Only a few studies reported findings for WC and PCa‐specific mortality, which varied from no association 23,24 to a positive association 3,6 .…”
Section: Introductioncontrasting
confidence: 89%
“…Moreover, more active screening behaviour in normal weight men compared to men with obesity may be involved. In our aforementioned study, we found that the negative association between BMI and the risk of localised PCa was partially driven by PCa cases detected through asymptomatic testing, 5 which supports a role for detection bias in the obesity–PCa association. To the best of our knowledge, no other prospective study has tested the prevailing hypothesis that the negative association between adiposity and the risk of localised PCa may be partly driven by localised PCa cases detected through PSA‐testing.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations